The role of Islamic Philanthropy in Economic Reconstruction: Systematic Literature Review and Bibliometric Analysis - Kastiah Ningrum Nurfitriani; Dea Ayu Elena Rahmawati; Purwanto; Yussi Ardhilla; Luqman Hakim; Choirul Anwar (Universitas Negeri Padang, 2026)
Despite the significant potential of Islamic philanthropy, a structural gap persists in its integration into global economic reconstruction policies. This study aims to synthesize a contemporary framework of Islamic philanthropy that synergizes Sharia distributive principles with modern digital efficiency. Following PRISMA guidelines, an initial 17,858 Scopus-indexed records (2021–2026) were filtered down to a metadata framework of 1,044 core documents. Bibliometric analysis was executed via VOSviewer using full-counting keyword co-occurrence to construct network and density visualizations. To ensure deep contextual relevance for qualitative synthesis, a rigorous full-text screening based on strict exclusion criteria filtered the sample to a final 24 high-quality articles. Moving beyond descriptive analysis, the primary contribution of this study is the development of the 4ER Model (Economic Rescue, Recovery, Reinforcement, and Resilience). The model’s novelty lies in its structural, multi-phase operational design that dynamically transitions marginalized beneficiaries (mustahik) into socio-economic contributors (muzakki). The findings demonstrate that integrating ZISWAF with digital innovations like AI and fintech optimizes distribution transparency and quality control. Ultimately, this study contributes a systemic framework proving that sustainable economic reconstruction depends on utilizing Islamic social finance as a fundamental, non-conventional stabilizer to bridge the global SDG financing gap.